2009
DOI: 10.1097/olq.0b013e318191701c
|View full text |Cite
|
Sign up to set email alerts
|

Normalizing HIV Testing in a Busy Urban Sexually Transmitted Infections Clinic

Abstract: After the introduction of several changes in clinic procedures, we experienced an increase HIV testing uptake relative to routine syphilis testing. In STI clinics, HIV testing can be made as normal as other routine STI testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…5,[11][12][13][14] Physician barriers to HIV testing include insufficient time, burdensome consent process, lack of knowledge/training about HIV testing and the CDC revised recommendations, difficulty locating HIV testing consent forms, lack of patient acceptance, competing priorities, and inadequate reimbursement. 15,16 A growing body of research has examined efforts to improve HIV testing rates in a variety of health-care settings, including a public, urban medical care system, 17 U.S. Department of Veterans Affairs health-care facilities, 18,19 hospital emergency departments, 20 a sexually transmitted disease (STD) clinic, 21 and community health centers (CHCs). [22][23][24] However, while studies of CHCs have described programs to implement routine testing and largely reported patient-level data, little research to date has examined barriers to implementation among CHC personnel.…”
mentioning
confidence: 99%
“…5,[11][12][13][14] Physician barriers to HIV testing include insufficient time, burdensome consent process, lack of knowledge/training about HIV testing and the CDC revised recommendations, difficulty locating HIV testing consent forms, lack of patient acceptance, competing priorities, and inadequate reimbursement. 15,16 A growing body of research has examined efforts to improve HIV testing rates in a variety of health-care settings, including a public, urban medical care system, 17 U.S. Department of Veterans Affairs health-care facilities, 18,19 hospital emergency departments, 20 a sexually transmitted disease (STD) clinic, 21 and community health centers (CHCs). [22][23][24] However, while studies of CHCs have described programs to implement routine testing and largely reported patient-level data, little research to date has examined barriers to implementation among CHC personnel.…”
mentioning
confidence: 99%
“…In a Denver STD clinic, HIV testing increased 1.2% because 79% of patients tested for syphilis were already being tested for HIV before the intervention. 10 Expectations of an HIV testing intervention’s magnitude should be tempered by the limits of the setting, which can be dictated by pre-existing HIV testing and case detection levels. In contrast to the STD clinic setting, an opt-out HIV testing program in a North Carolina emergency department with low pre-intervention levels of HIV testing during this same time period resulted in a 173% increase in HIV testing.…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive HIV treatment and care programs organized by the Chinese government demonstrate high-level commitment to HIV control. Promising pilot programs integrating HIV testing at STD clinics have been implemented in the US 32 and Europe. 33 As China’s HIV epidemic increasingly involves sexual transmission, HIV testing at STD clinics and other locations where high-risk individuals seek sexual health services is important.…”
Section: Discussionmentioning
confidence: 99%